TANTANGAN EKONOMI SYARIAH DALAM MENGHADAPI MASA DEPAN INDONESIA DI ERA GLOBALISASI - Anis Mashdurohatun (Jurnal Dinamika Hukum, 2011)
In essence, globalization is the best means for Muslims to introduce the culture and the teachings of Islam to all corners of the world. Islamic economic challenges including the State that in fact many Muslim population tends to use the capitalist system; In economics and politics in view of the Islamic State is not strong so it is difficult to prove that the Islamic Economic System is superior to the capitalist and socialist, and Among the experts was still disagreement on the definition Islamic Economic System. Islamic Economy Facing Future In Indonesia in the Era of Globalization needs to consider several factors, namely Mastery Technologies, Sharia-based SME Development, Keeping the Sharia Economic Excellence, namely Islamic economic system, and also the prohibition of usury.Keywords:  islamic economic, globalization, capitalism